In Vitro and Ex Situ Biodegradation of Low-Density Polyethylene by a Rhizopus sp. Strain Isolated from a Local Dumpsite in North-East Algeria: 10.32526/ennrj/20/202200026 - Harrat, Randa; Bourzam, Ghania; Ouled-Haddar, Houria; Soumati, Boudjema (Environment and Natural Resources Journal, 2022)
Low density polyethylene (LDPE) is the most abundant non-degradable plastic waste. Widely used in packaging material, it represents a serious threat to all ecosystems. In the present study, a Rhizopus sp. fungal strain was isolated from soil of a landfill located in north-east Algeria and cultured on potato dextrose agar. The in vitro biodegradability of pieces of the same plastic bag (0.2, 0.4, and 0.6 g) was estimated in minimal liquid medium and on minimal solid medium. Furthermore, biodegradation of plastic bag pieces was examined in seawater, tap water and soil. The isolated Rhizopus sp. strain could degrade the plastic bag waste. The highest in vitro rate occurred in the minimal liquid medium for both the 0.4-g and 0.6-g pieces (a 20% decrease in weight). In natural media, the highest weight decrease was different depending on the substrate: 5% in seawater for the 0.2-g piece, 10% in tap water for the 0.4-g piece and 8% in soil for the 0.4-g piece. This strain could also form a biofilm in Malt Extract Broth (MEB). These results revealed that the isolated Rhizopus sp. strain has considerable biodegradative ability based on different measures.